Promotion of Problem Solving Skills by Using Metacognitive-based Instruction in Students of Kermanshah University of Medical Sciences - yahya safari; habibeh meskini; akba nosrati (Zanjan University of Medical Sciences and Health Services, 2017)
Background and objective: Studies have indicated that metacognitive strategies control and direct cognitive strategies. Thus, application of metacognitive and cognitive strategies together is essential for successful learning to happen. The present study was conducted to examine the effect of metacognitive-oriented instruction on development of problem solving skills in students of Kermanshah University of Medical Sciences. Materials and Methods: This study was a quasi-experimental research with pretest/posttest and control group design. The study sample included the students of Kermanshah University of Medical Sciences (n=4283) in the academic year of 2013-2014. A total number of 40 students were selected through convenient sampling method as the study sample. The samples were randomly placed in experimental and control groups. For the experimental group, problem solving skills were taught based on metacognitive strategies in 8 sessions, each session for 1 and half hours. For the control group, however, problem solving skills were taught through conventional teaching method. The instrument for data collection was Heppner's problem solving inventory (1988) whose validity and reliability were confirmed previously. Data were analyzed by descriptive statistics, mean and standard deviation, and the hypotheses were tested through t-test. Results: The results of the posttest showed that the total mean of scores for problem solving skills in the experimental group (99.75) was higher than that of the control group (26.800) (p<0.0001). This difference was significant in the case of confidence, approach/avoidance and personal control components (p<0.0001). Moreover, the mean of students' scores was not significant in terms of gender and major. Conclusion: Given the positive effect of metacognitive strategies on the students' performance and the necessity of teaching metacognition for the sake of academic achievement, these strategies are recommended to be taught to students. Keyword: Metacognition, Problem-solving skill, Metacognition instruction, Medical students.